2015
DOI: 10.1016/j.apmr.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior in the First Year After Stroke: A Longitudinal Cohort Study With Objective Measures

Abstract: Stroke survivors were highly sedentary and remained so a year after stroke independently of their functional ability. Developing interventions to reduce sedentary behavior might be a potential new therapeutic target in stroke rehabilitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
98
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 160 publications
(114 citation statements)
references
References 41 publications
13
98
0
3
Order By: Relevance
“…In the present study, the incidence of dysphagia found, considering the factor of VCA presence, was of 94%, according to the classification of the DOSS (7) scale, corroborating the incidence studies. The predominance regarding age above 70 years and occurrence of VCA in individuals of male gender found in this study is pertinent to the one found in literature (12)(13)(14)(15)(16) . The speech-language pathologist follow up on the dysphagia patient requires the discussion with the multi professional team regarding the indication of indirect therapies (without food introduction) or direct (with the use of food), related to the releasing moment of the oral intake in a systematic way, the indication of full oral intake diet, with the possibility of weaning of the alternative feeding intake.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…In the present study, the incidence of dysphagia found, considering the factor of VCA presence, was of 94%, according to the classification of the DOSS (7) scale, corroborating the incidence studies. The predominance regarding age above 70 years and occurrence of VCA in individuals of male gender found in this study is pertinent to the one found in literature (12)(13)(14)(15)(16) . The speech-language pathologist follow up on the dysphagia patient requires the discussion with the multi professional team regarding the indication of indirect therapies (without food introduction) or direct (with the use of food), related to the releasing moment of the oral intake in a systematic way, the indication of full oral intake diet, with the possibility of weaning of the alternative feeding intake.…”
Section: Discussionsupporting
confidence: 75%
“…The lack or presence of aspiration has been one of the video fluoroscopic signals of higher relevance, being this signal essential for decision making at the management of oral food intake and for the indication of the most adequate consistency in each case (9)(10)(11)(12)(13)(14)(15)(16)(17) . The aspiration incidence in VCA neurogenic dysphagia framework is described in studies between 155 and 50% (18,19) .…”
Section: Discussionmentioning
confidence: 99%
“…Although the stroke group had statistically more participants at level I according to MRC (" I only get breathless with strenuous exercise"), it seems that this result does not positively affect the PA level in the stroke group when compared to the healthy group. There are some studies using accelometers that proved a low PA level of stroke patients (12,31). As pedometers were also found feasible to evaluate the PA level of stroke patients (22,32), we preferred to use a pedometer and found that the step count and walking distance in the stroke group were significantly less than those in the healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of activities is an increasingly used parameter in studies of people with chronic conditions (6). However, there is growing evidence (14)(15)(16)21) to support that it is not only the amount of a given activity that is important, but also how periods of activity are distributed in bouts of shorter or longer duration. Distribution has been studied for periods of physical activity, but also for sedentary behaviour, being an independent risk factor for chronic disease and poor health outcomes (22).…”
Section: Introductionmentioning
confidence: 99%